Modification of structure of the surface of steel (ХГС) as a result of influences of high-current electron beam - Prokhorenko, E.M.; Lytvynenko, V.V.; Melyakovа, O.А.; Lonin, Yu.F.; Ponomarev, A.G.; Uvarov, V.T.; Shul'gin, N.A.; Prokhorenko, T.G. (Вопросы атомной науки и техники, 2020)
The steel surface (ХГС) was irradiated with a high-current electron beam. A high-current electron beam was obtained in the TEMP-A accelerator. Steel samples were made from drum mill balls. The balls had varying degrees of wear. The mechanical and microstructural characteristics were studied. Applied methods: measurement of hardness, tensile strength, fractographic and metallographic analysis. An increase in hardness was found for all samples. An increase in the surface hardness of the samples occurred as a result of the conversion of austenite to martensite and lower bainite. A significant effect on the increase in surface hardness of the samples is also exerted by the process of the appearance of carbides.